Outcome Measurements for Pain Relief in Elderly Patients with Spinal Stenosis Undergoing Epidural Steroid Injection: Is Conservative Approach an Option? - Tasdogan, Ali Muhittin; Tarikci Kilic, Ebru (TURKISH NEUROSURGICAL SOC, 2020)
AIM: To evaluate the short-term outcomes of epidural steroid injections (ESIs) among elderly patients with lumbar spinal stenosis. MATERIAL and METHODS: This was a retrospective study. The sample consisted of 44 patients aged 65 or older who underwent epidural steroid injections secondary to lumbar spinal stenosis between 2014 and 2016 at a single center. Data were collected using the Numeric Rating Scale (NRS), Oswestry Disability Index (ODI), and Istanbul Low Back Pain Disability Index (ILBPDI) before and at 3-month follow-up visit. RESULTS: Participants had lower mean scale scores at all times after ESI administration than before. Four patients (9.1%) needed additional injections while two (4.5%) needed operation. No minor or major ESI-related complications were observed. CONCLUSION: Epidural steroid injections are an effective nonsurgical option for pain relief and improvement of physical function in elderly patients. The NRS, ODI, and ILBPDI are reliable and valid scales that can be used to evaluate the outcomes of ESIs in a selected group of elderly patients.
Keywords: Elderly; Epidural steroid injection; Lumbar spinal stenosis; Low back pain; Pain relief